Caracterização anato-fisiológica de Cattleya guttata Lindl. e Laelia tenebrosa Rolf. (orchidaceae): efeito da radiação - Costa, Thaís Silva (2014)
This study aimed to investigate the leaf anatomical structure of Laelia tenebrosa Rolf. and Cattleya guttata Lindl. and subsequently verify acclimation capacity of these species through physiological responses shown by them towards an environment with higher light intensity. 5 randomly selected plants of each species and each individual withdrew a fully expanded leaf were used for anatomical description. For the analysis of chlorophyll a fluorescence transient, 6 treatments were used in each kind: day 0 (fluorescence measurement performed in the nursery João Neiva / ES with photon flux density of 300 micromol m-2 s-1), 1 day, 3 days, 7 days, 11 days and 95 days after transfer of the plants into the greenhouse CEUNES (photon flux density was 1225 ol m-2s-1). Anatomical analysis of leaves detected the occurrence of characters that can be interpreted as adaptations to water and structural maintenance of leaf economy. Both are hypostomatic exhibit stomatal pore-protected by projections, vascular bundles surrounded by pericyclic fibers and thick epidermal cuticle on both leaf surfaces. In addition to these characteristics, C. guttata, in its anatomical structure, showed a high density of stomata, adaxial cuticle thicker and thicker wall hypodermic L. tenebrosa. The analysis of transient OLKJIP and parameters of the JIP-test indicated the end of the period of 95 days in an environment with higher incidence of light acclimation of both species. It was observed that the species C. guttata and L. tenebrosa showed no photochemical damage mechanisms related to the FSI and FSII. In this sense, perhaps the anatomical structures presented by the studied species contributed to the plants did not suffer severe damage to their photochemical apparatus when transferred to an environment with higher luminosity